2017
DOI: 10.1103/physreve.95.042140
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of complexity and pattern manipulation

Abstract: Many organisms capitalize on their ability to predict the environment to maximize available free energy, and reinvest this energy to create new complex structures. This functionality relies on the manipulation of patterns-temporally ordered sequences of data. Here, we propose a framework to describe pattern manipulators -devices that convert thermodynamic work to patterns or vice versa -and use them to build a 'pattern engine that facilitates a thermodynamic cycle of pattern creation and consumption. We show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 47 publications
2
43
1
Order By: Relevance
“…6. This also allows one to appreciate that pattern generators previously thought to be asymptotically efficient are actually quite dissipative [27]. Taken altogether, these results provide guideposts for designing efficient, modular, and complex information processorsguideposts that go substantially beyond Landauer's principle for localized processing.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…6. This also allows one to appreciate that pattern generators previously thought to be asymptotically efficient are actually quite dissipative [27]. Taken altogether, these results provide guideposts for designing efficient, modular, and complex information processorsguideposts that go substantially beyond Landauer's principle for localized processing.…”
Section: Introductionmentioning
confidence: 80%
“…It was previously shown that storing unnecessary information about the past leads to additional transient dissipation when generating a pattern [27,53]. This cost also arises from implementation.…”
Section: Retrodictive Generatorsmentioning
confidence: 99%
See 3 more Smart Citations